The impact of investments on the economic performance of Borsod-Abaúj-Zemplén county in relation to the 2014-2020 European Union development cycle - Gál, Boglárka Bánné (Észak-magyarországi Stratégiai Füzetek, 2025)
In my study, I examined the territorial dimensions of Hungary's economic performance between 2013 and 2021. The choice of the time interval was based on a conscious methodological choice. The evaluation of the EU development cycle 2014-2020 requires knowledge of the economic situation before that period, so it was justified to choose 2013 as the starting year. This year can be considered as a record of the situation prior to the allocation of development funds, which provides a basis for an objective assessment of the economic situation prior to the interventions. The year 2021 was used as the upper limit for the period under consideration, as it already partly reflects the economic impact of the investments of the 2014-2020 development cycle. EU funds often have a multi-stage, longer-term impact on the local economy, so a timeframe beyond one year is necessary to measure results (ESF, 2018). Thus, analysing the period up to 2021 provides an opportunity to examine the after-effects of the funds in more detail and to capture structural changes.